PENGARUH SERANGAN KUMBANG AMBROSIA XYLEBORUS SP. TERHADAP KUALITAS KAYU TUSAM (PINUS MERKUSII). - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
Some green logs of tusam (Pinus merkusii Jungh et de Vr.) infested by the ambrosia beetle Xyleborus sp. were obserbed. About one thousand lunnels per-square meter were shown on the entire surface of each log. The beetle bored direclly into the logs, causing wood damage.The damaged grades of sawntimbers converted from the infested logs showed varied. The most langential sawtimber was highly affected, bul by then the damage decreased very sharply toward the radial area in accordance with a regression equation : Y = 1840. 70 - 546. 63. lnX r = 0.98where X = depth of sawntimber surface measured fram the most tangential area (cm). Y = number of tunnels per-square meter.The infested area of the wood was mostly in the peripheral part of the logs. Of an observed log, it showed thet in average of 991,.48 lunnels per-square meter appeared in a 5 cm thickness of that part, and then 231.54 and 9. 73 tunnels per-square meter in the consecuuve second and third 5 cm of the inner pan. the wood part of more than 15 cm in depth remained intack.